The Impact of COVID-19 Pandemic on Arthropod-Related Diseases - Vahideh Moin-Vaziri; Mehdi Badakhshan (Tehran University of Medical Sciences, 2023)
Background: The Covid-19 pandemic that caused by the infection with the novel Coronavirus SARS-CoV-2 has revealed individual and global vulnerabilities all over the world. Many countries that had been struggled with arthropod-borne diseases (VBDs) are now embroiled in another challenge caused by COVID-19 pandemic. The situation that poses major obstacles 1) by misdiagnosis 2) delay in early and appropriate treatment of VBDs 3) difficulties in applying regular strategy for vector control and prevention methods and finally 4) irregularity in financing supports. Given the possible scenario of syndemics, it is important to plan integrated and combined measurement with the maximum participation of the people and health authorities. Here, the impact of COVID-19 pandemic on some major arthropod-related diseases will be discussed. Methods: To access the collective data all related databases such as Science direct, PubMed, Elsevier, Google scholar, as well WHO web page were searched with key words "arthropoda-related diseases, COVID-19 with the name of each individual disease". Results: The results showed that the management, control, and treatment of most important arthropod-related diseases could be delayed due to COVID-19 pandemic. Conclusion: Dealing with COVID-19, it is crucial to consider the other main killers such as malaria, dengue fever, etc. more especially in vulnerable populations by greater political, financial and global commitment. Continued surveillance will be essential to monitor for any possible changes.